Utilization of AHP-TOPSIS Combination to Determine The Best Biomass Dryer Technology at Pelabuhan Ratu CFPP - Hermawan, Heru (Journal of Mechanical Design and Testing, 2025)
The main challenge of biomass cofiring at Pelabuhan Ratu Power Plant is the high moisture and low calorific value of the biomass (sawdust). This biomass characteristic causes low green energy production despite high biomass utilization. Meanwhile, the green energy production target continues to increase in the upcoming year, according to PLN's Cofiring Roadmap. This research focuses on the selection of biomass dryers using Multi-Criteria Decision Making, including rotary dryers, packed moving bed dryers, and flash dryers. The method used was the Analytical Hierarchy Process (AHP) and Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) using four criteria and eight sub- criteria. Seven experts were asked to complete the criteria ranking questionnaire for AHP input. Other relevant data were also collected, such as operational data, risk management, internal discussions, literature studies, and others. The top 3 criteria with the highest global weight (AHP results) are Biomass Characteristics (28.1%), Safety (20.5%), and Environment (17.8%). TOPSIS calculation resulted in the rotary dryer being the best alternative biomass dryer. Furthermore, a sensitivity test was conducted by changing the weight of each of the top 3 criteria by -25% and +25%. The results show that the rotary dryer is consistently the best alternative.